The Effectiveness of the Assignment Method in Civic Education Courses on the Learning Outcomes Of Students of the Diploma 4 Study Program Majoring in Computer Engineering at the Sriwijaya State Polytechnic - Liza Utama*; Ayu Puspasari; Dewi Indasari; Aimi Aimi (Riwayat: Educational Journal of History and Humanities, 2023)
In the learning process there are various teaching methods, one of which is the assignment method. The method of giving assignments can be given by teachers (lecturers) to students as one of the bases for assessing student learning outcomes. The problem in this research is how the effectiveness of the assignment method in civic education courses on the learning outcomes of students of the diploma 4 study program majoring in computer engineering at the Sriwijaya State polytechnic?. This study aims to determine the effectiveness of the assignment method in the Citizenship Education course on student learning outcomes in the diploma 4 study program, majoring in computer engineering, Sriwijaya State Polytechnic. The research method used in this research is descriptive quantitative. The sample in this study was taken by purposive sampling. The sample in this study were students of class 6TIA and 6TIB Diploma 4 study program majoring in computer engineering, Sriwijaya State Polytechnic. Where the number of students in class 6TIA is 19 people, while students in class 6TIB are 20 people. The data used in this study are primary data and secondary data. Primary data is obtained through assessment of student learning outcomes and secondary data is obtained through various sources of literature. The data analysis technique in this study was to use the Paired-Sample T test method, namely to test whether there were differences in student learning outcomes before and after the study was carried out. The results showed that there was the effectiveness of the assignment method in the Citizenship Education course on student learning outcomes in the diploma 4 study program of computer engineering majors Sriwijaya State Polytechnic.